Education for democratic intercultural citizenship - Veugelers, Wiel (Moral development and citizenship education, 2019)
"Education for Democratic Intercultural Citizenship (EDIC) is very relevant in contemporary societies. All citizens, but in particular teachers, curriculum developers, educational policy makers, and educational professionals in civil society (NGOs) have a crucial role in this. Seven European universities are working together in developing a curriculum to prepare their students for this important academic, societal and political task. As part of an Erasmus+ Strategic Partnership they each develop a module in the area of moral, intercultural and citizenship education. All modules are international and inquiry oriented, and make links with society. In this book the leading scholars write the theoretical background of their module, their curriculum guidelines and goals, the concrete programmes, and the experiences of students. The universities had an annual intensive programme in which students and teachers of all universities came together to have try-outs of parts of the modules. These programmes contributed strongly to the network building of researchers, teachers and students. The activities have given a strong stimulus to the implementation of Education for Democratic Intercultural Citizenship in the participating universities and in educational organisations worldwide. The experiences show both the necessity and the relevance of this topic and this kind of collaboration"--